2015
DOI: 10.1007/s10886-015-0612-8
|View full text |Cite
|
Sign up to set email alerts
|

The Scent Glands of the Neotropical Harvestman Discocyrtus pectnifemur: Morphology, Behavior and Chemistry

Abstract: Harvestmen have a pair of scent glands that open through ozopores. The literature suggests a link between the morphology of the ozopore area and the emission of a defensive secretion. A previous study on a species that aggregates in open areas, where individuals are probably more easily spotted by predators, showed that this defensive secretion causes conspecifics to flee. However, it is unknown whether this behavior occurs in species that aggregate in sheltered areas, where prey are harder to find. Herein, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…This sexual variation may reflect the fact that female harvestmen may use chemical defenses more often than males (Segovia, Murayama, & Willemart, 2018), and thus they may have ozopores that are easier to access or produce more secretions, while males may rely more upon physical defenses. Although we did not observe any significant sexual differences in ozopore morphology, recent studies have revealed intraspecific variation in the mode and frequency of the release of scent gland secretions (Moore & Townsend Jr., 2019;Nazareth & Machado, 2015;Segovia et al, 2015Segovia et al, , 2018.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This sexual variation may reflect the fact that female harvestmen may use chemical defenses more often than males (Segovia, Murayama, & Willemart, 2018), and thus they may have ozopores that are easier to access or produce more secretions, while males may rely more upon physical defenses. Although we did not observe any significant sexual differences in ozopore morphology, recent studies have revealed intraspecific variation in the mode and frequency of the release of scent gland secretions (Moore & Townsend Jr., 2019;Nazareth & Machado, 2015;Segovia et al, 2015Segovia et al, , 2018.…”
Section: Discussioncontrasting
confidence: 94%
“…Hara and Gnaspini (2003) noted three mechanisms for the release of scent gland secretions including the evaporation of chemicals from the immediate vicinity of the ozopore, the production of a fine spray or liquid from the ozopore that spreads over the body (forming a chemical shield), or the specific direction of the scent gland secretions by jet emission or by leg dabbing (see Eisner, Jones, Hicks, Silberglied, & Meinwald, 1977;Eisner, Kluge, Carrel, & Meinwald, 1971). Recent studies have found that the frequency of the use of scent gland secretions vary between ovigerous and non-ovigerous females (Nazareth & Machado, 2015) and that at least some species of harvestmen exhibit intraspecific variation with respect to the mechanism of secretion (Moore & Townsend Jr., 2019;Segovia, Hara, Pagoti, & Sannomiya, 2015).…”
mentioning
confidence: 99%
“…Harvestmen are well known for their repugnatorial glands and defensive chemicals (Gnaspini & Hara, 2007;Raspotnig et al, 2014;Segovia et al, 2015a). However, it has been reported that, unexpectedly, such secretions are not used against all predators: in more than a hundred interactions between armored harvestmen and spiders, only a single harvestman released defensive secretions (Souza & Willemart, 2011;Carvalho, Souza & Willemart, 2012;Dias & Willemart, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Harvestmen (Arachnida, Opiliones) are mostly nocturnal organisms known for their chemical defenses (Gnaspini & Hara, 2007;Nazareth & Machado, 2015;Segovia et al, 2015a), but that actually have an array of defensive mechanisms. For some species of the suborder Laniatores, a thick armor is the primary defense mechanism (Souza & Willemart, 2011;Dias & Willemart, 2013;Segovia, Del-Claro & Willemart, 2015b), but they may also freeze (Chelini, Willemart & Hebets, 2009), flee or retaliate both chemically and mechanically, during which they may bite and pinch with their chelicerae or pedipalps and pinch with spines on legs IV (Gnaspini & Hara, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Harvestmen have two main strategies of transmitting defensive compounds: (1) create a chemical shield around the body, and (2) direct the liquid toward the offending agent, i.e. 'jet emission' (Segovia et al 2015). These strategies are variable among harvestmen (Gnaspini & Hara 2007).…”
Section: Transmission Of Chemical Signals In Harvestmenmentioning
confidence: 99%